Efektivitas Model PjBL terhadap Keterampilan Kolaborasi Mahasiswa pada Perkuliahan Statistik Penelitian - Islawati, Islawati; Samsuddin, Yati Bt (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to examine the effectiveness of the Project-Based Learning (PjBL) model in improving student collaboration skills in the Research Statistics course. Collaboration is defined as the ability to work harmoniously in a group to achieve a common goal. In the context of higher education, this skill is important to support students' readiness to face the world of work that demands the ability to work in a team. The research uses a quantitative descriptive approach, with data obtained through questionnaires and observation sheets. The measurement was carried out based on five dimensions of collaboration: effective communication, teamwork, division of tasks, joint problem-solving, and mutual respect. The research sample consisted of 22 students in the V semester, who were selected using the total sampling technique. Data analysis was carried out descriptively to calculate the average score of each dimension and its category based on a scale. The findings indicate that the PjBL model positively impacts students' collaboration skills, with significant improvements in the dimensions of mutual respect and teamwork (categorized as Very Good). However, the task distribution dimension requires further attention due to gaps in group responsibilities. These findings confirm that PjBL is effective in bridging the gap between academic competencies and workforce demands, while also recommending the integration of active learning in higher education